Research on Science Communication: What is Known and What Needs To Be Known - James E. Grunig (Journal of Applied Communications, 1979)
We have a great deal of research data on problems of science communication, but few deep theories which structure that data into an integrated picture of the nature of science communication and how best to carry it out. (Papers from the National Agricultural Science Information Conference, Ames, Iowa.)